(untitled) (Journal of Bio-Science, 2014)
Context: Jatropha belongs the spurge family Euphorbiaceae. Special interest mounting for its biodiesel which has created enthusiasm in cultivation of the species for oil extraction. Objectives: The study was conducted to develop the protocol for tissue and callus culture in Bangladeshi Jatropha curcus plant particularly to identify the most suitable explants for its wide scale micropropagation. Materials and Methods: Immature embryos taken from four developmental stages of fruits were cultured on growth regulator free MS liquid medium. After fifteen days of germination, elongated hypocotyls and two cotyledonary leaves were used as explants. Results: Embryo derived seedlings acted as the potential source of explants both for callus and plantlets. The immature embryo of size 0.87cm produced highest callus formation (83.33%) on MS medium supplemented with lower concentration of 2, 4-D (0.5 mg/l) and coconut water 2% (v/v). Immature embryos grown on MS basal medium supplemented with 2,4-D (0.2 mg/l, 0.5 mg/l and 1.0 mg/l) alone or in combination with coconut water 2% (v/v) exhibited a wide range of callus induction percentage (26-100%) for hypocotyls and (20 - 40%) for cotyledonary leaves. Conclusion: The age of immature embryo and addition of growth adjuvants and growth additive to the culture medium played the role in promoting better callus and plantlet formation. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17726 J. bio-sci. 20: 125-134, 2012